Process evaluation protocol for a cluster randomised trial of a complex, nurse-led intervention to improve hypertension management in India. Issue 5 (19th May 2019) - Srinivasapura Venkateshmurthy, Nikhil; Mc Namara, Kevin; Koorts, Harriet; Mohan, Sailesh; S Ajay, Vamadevan; Jindal, Devraj; Malipeddi, Bhaskara Rao; Roy, Ambuj; Tandon, Nikhil; Prabhakaran, Dorairaj; Worsley, Tony; Maddison, Ralph; et al.
Abstract : Introduction: India has high prevalence of hypertension but low awareness, treatment and control rate. A cluster randomised trial entitled 'm-Power Heart Project' is being implemented to test the effectiveness of a nurse care coordinator (NCC) led complex intervention to address uncontrolled hypertension in the community health centres (CHCs). The trial's process evaluation will assess the fidelity and quality of implementation, clarify the causal mechanisms and identify the contextual factors associated with variation in the outcomes. The trial will use a theory-based mixed-methods process evaluation, guided by the Consolidated Framework for Implementation Research. Methods and analysis: The process evaluation will be conducted in the CHCs of Visakhapatnam (southern India). The key stakeholders involved in the intervention development and implementation will be included as participants. In-depth interviews will be conducted with intervention developers, doctors, NCCs and health department officials and focus groups with patients and their caregivers. NCC training will be evaluated using Kirkpatrick's model for training evaluation. Key process evaluation indicators (number of patients recruited and retained; concordance between the treatment plans generated by the electronic decision support system and treatment prescribed by the doctor and so on) will be assessed. Fidelity will be assessed using Borrelli et al 's framework. Qualitative data will be analysed using the template analysis technique. Quantitative data will be summarised as medians (IQR), means (SD) and proportions as appropriate. Mixed-methods analysis will be conducted to assess if the variation in the mean reduction of systolic blood pressure between the intervention CHCs is influenced by patient satisfaction, training outcome, attitude of doctors, patients and NCCs about the intervention, process indicators etc. Ethics and dissemination: Ethical approval for this study was obtained from the ethics committees at Public Health Foundation of India and Deakin University. Findings will be disseminated via peer-reviewed publications, national and international conference presentations. Trial registration number: NCT03164317 ; Pre-results.